The implication of school admission rules for segregation and educational inequality: Research report - Robert Aue; Maximilian Bach; Julia Heigle; Thilo Klein; Friedhelm Pfeiffer; Kristina Zapp (ZEW - Leibniz Centre for European Economic Research (ZEW), 2020)
In this research project we investigate how the design of school assignment rules affects social segregation and its implications for social inequality. The context of our study is the Hungarian school system, which is characterized by early ability tracking combined with a centralized assignment mechanism based on the student-proposing deferred-acceptance algorithm. The project is split into three interrelated parts. First, we investigate the different factors that affect social segregation through the school assignment process. Second, we analyze how segregation resulting through school assignments affects inequality in student achievement. In a final step, we plan to combine insights from the first two parts in a counterfactual analysis to evaluate different assignment rules.
Keywords: 330; Social exclusion; educational opportunities; school policy; Hungary; Soziale Ausgrenzung; Bildungschancen; Schulpolitik; Ungarn